2010
DOI: 10.1152/ajplung.00347.2009
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine production of TGF-β1 promotes myofibroblastic differentiation of neonatal lung mesenchymal stem cells

Abstract: We have isolated mesenchymal stem cells (MSCs) from tracheal aspirates of premature infants with respiratory distress. We examined the capacity of MSCs to differentiate into myofibroblasts, cells that participate in lung development, injury, and repair. Gene expression was measured by array, qPCR, immunoblot, and immunocytochemistry. Unstimulated MSCs expressed mRNAs encoding contractile (e.g., ACTA2, TAGLN), extracellular matrix (COL1A1 and ELN), and actin-binding (DBN1, PXN) proteins, consistent with a myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 46 publications
7
87
0
1
Order By: Relevance
“…There was no difference in latent TGF-β between groups (no BPD, 223±133 pg/ml, 0.24±0.13 pg/ng scIgA; BPD, 255±183 pg/ml, 0.30±0.26 pg/ng scIgA; mean±SD). On the other hand, normalized TGF-β levels were higher in patients with MSCs (cell-negative, 162± 113 pg/ml, 0.129±0.096 pg/ng scIgA; cell-positive, 263±163 pg/ml, 0.317±0.209 pg/ng scIgA, p=0.038), consistent with our finding that MSCs produce TGF-β 11 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…There was no difference in latent TGF-β between groups (no BPD, 223±133 pg/ml, 0.24±0.13 pg/ng scIgA; BPD, 255±183 pg/ml, 0.30±0.26 pg/ng scIgA; mean±SD). On the other hand, normalized TGF-β levels were higher in patients with MSCs (cell-negative, 162± 113 pg/ml, 0.129±0.096 pg/ng scIgA; cell-positive, 263±163 pg/ml, 0.317±0.209 pg/ng scIgA, p=0.038), consistent with our finding that MSCs produce TGF-β 11 .…”
Section: Resultssupporting
confidence: 90%
“…We also observed that MSCs express mRNAs encoding contractile and extracellular matrix proteins, consistent with a myofibroblast progenitor phenotype. Treatment of MSCs with TGF-β induced myofibroblastic differentiation 11 . We therefore reasoned that MSCs are more likely to be isolated from the tracheal aspirates of premature infants who develop BPD than those who do not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-384-5p is a marker of neurotoxicity and regulates apoptotic cell death in myocardial ischemia by modulating PIK3CD pathway (26). Myosin heavy chain 11 is a component of the contractile apparatus of aortic smooth muscle cells and is expressed in neonatal lung smooth muscle cells (27). RNF44 is a poorly understood protein that is encoded by a gene and contains a RING finger motif, a motif often present on proteins involved in protein-protein and protein-DNA interactions.…”
Section: Articlesmentioning
confidence: 99%
“…117,118 Conflicting reports also exist about mesenchymal stromal cells, depending on the source. [119][120][121] These findings highlight the importance of appropriately defining these progenitor cells and whether their function is altered because of their origin (lung, umbilical cord, bone marrow). Yet therapeutic administration of progenitor cells for the prevention or treatment of BPD holds significant promise, as several studies have shown benefit in experimental models.…”
Section: Pvd In Bpdmentioning
confidence: 97%